P054 Monocyte-related biomarkers of rheumatoid arthritis development in undifferentiated arthritis patients – a pilot study. (21st February 2018) - Kurowska, W; Kuca-Warnawin, E; Radzikowska, A; Maslinska, M; Kwiatkowska, B; Maslinski, W
Abstract : Introduction: The enhanced/disturbed activities of monocytes are important for perpetuation and for development of rheumatoid arthritis (RA). Therefore, consistent analysis of monocytes activities and regulation of molecular pathways operating within monocytes, especially at early stages of RA development, may help to predict the progression to the full-blown disease. Objectives: In this study we aimed to investigate the profile of miRNAs expression in circulating monocytes and monocyte-related cytokines in peripheral blood of individuals at undifferentiated arthritis (UA) stage as potential new biomarkers for RA development. Methods: Magnetically sorted monocytes from peripheral blood (PB) of 20 individuals with UA served for total RNA isolation. RNA samples were used for microRNA profiling performed on the miRCURY LNA array. Concentrations of CCL3/MIP-1a, M-CSF, CCL2/MCP-1, IL-6, TNFa, IL-15 and eotaxin in sera of UA patients were measured using commercial ELISA assays. Verification of diagnosis after 4 years of follow-up led to the identification of patients who developed full-blown RA (UA→RA patients) and patients who remained in UA phase (UA→UA patients). Comparisons between patients groups were performed using two tailed Mann Whitney U test. Results: Following computational unsupervised analysis we identified 50 miRNAs in PB monocytes that have the largest variation of expression across all patients samples. From these 50 miRNAs, expression of three miRNAs: miR-642b-5p (p=0.0380), miR-483–3 p (p=0.009), miR-371b-5p (=0.0381) were up-regulated, and two miRNAs: miR-25–3 p (=0.0317) and miR-378d (p=0.0059) were down-regulated in monocytes from UA→RA vs UA→UA patients. This specific pattern of miRNAs expression in circulating monocytes paralleled elevated IL-15 (p=0.003) and M-CSF (p=0.03) concentrations in sera of UA patients who progressed to RA. Conclusions: Our results indicate that altered activity of monocytes can be detected at early stages of RA development. We found new miRNA candidates (miR-642b-5p, miR-483–3 p, miR-371b-5p, miR-25–3 p and miR-378d) differentially expressed in PB monocytes, and elevated concentrations of circulating IL-15 and M-CSF involved in monocyte activity and differentiation, as potential biomarkers identifying UA patients who subsequently developed RA. Acknowledgements: This work was sponsored by grant No: UMO-2011/03/B/NZ6/05035 from National Science Centre and Polish Ministry of Science and Higher Education (core grant S/17). Disclosure of interest: None declared